Effect of type of luting agents on stress distribution in the bone surrounding implants supporting a three-unit fixed dental prosthesis: 3D finite element analysis - Ehsan Ghasemi; Alireza Abedian; Pedram Iranmanesh; Saber Khazaei (Dental Research Journal, 2015)
Background: Osseointegration of dental implants is influenced by many biomechanical factors that may be related to stress distribution. The aim of this study was to evaluate the effect of type of luting agent on stress distribution in the bone surrounding implants, which support a three-unit fixed dental prosthesis (FDP) using finite element (FE) analysis. Materials and Methods: A 3D FE model of a three-unit FDP was designed replacing the maxillary first molar with maxillary second premolar and second molar as the abutments using CATIA V5R18 software and analyzed with ABAQUS/CAE 6.6 version. The model was consisted of 465108 nodes and 86296 elements and the luting agent thickness was considered 25 μm. Three load conditions were applied on eight points in each functional cusp in horizontal (57.0 N), vertical (200.0 N) and oblique (400.0 N, θ = 120°) directions. Five different luting agents were evaluated. All materials were assumed to be linear elastic, homogeneous, time independent and isotropic. Results: For all luting agent types, the stress distribution pattern in the cortical bone, connectors, implant and abutment regions was almost uniform among the three loads. Furthermore, the maximum von Mises stress of the cortical bone was at the palatal side of second premolar. Likewise, the maximum von Mises stress in the connector region was in the top and bottom of this part. Conclusion: Luting agents transfer the load to cortical bone and different types of luting agents do not affect the pattern of load transfer.